1971
DOI: 10.1111/j.1469-8137.1971.tb02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies ON MUTUALISTIC SYMBIOSIS BETWEEN SYCONIA AND SYCOPHILOUS WASPS IN MONOECIOUS FIGS

Abstract: SUMMARYThe constituents of a normal monoecious fig, namely the male and female flowers, the shortand long-styled female flowers and the male and feinale wasp galls, are arranged in deflnite spatial and numerical relations. The normal development of the syconium depends on a balance of these difl^erent elements. Occasionally various types of aberrant figs are found in nature, differing from normal figs in development and in flnal structure. These are purely gall figs, seed figs and male wasp or female wasp figs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 10 publications
5
58
0
1
Order By: Relevance
“…Therefore, style length is not causal factor explaining the abundance of unexploited flowers. We found higher production of galls in the cold season (Figure 2), with up to 60% of female flowers giving rise to galls, which confirms previous observations that pollinators can oviposit in most female flowers in both Ficus sycomorus [22,32] and other figs [11].…”
Section: Resultssupporting
confidence: 78%
“…Therefore, style length is not causal factor explaining the abundance of unexploited flowers. We found higher production of galls in the cold season (Figure 2), with up to 60% of female flowers giving rise to galls, which confirms previous observations that pollinators can oviposit in most female flowers in both Ficus sycomorus [22,32] and other figs [11].…”
Section: Resultssupporting
confidence: 78%
“…The oviposition of non-pollinating fig wasps on F. eximia prevented unpollinated figs from aborting (table 2), as observed in other studies (Galil & Eisikowitch 1971, Bronstein 1991, Compton & vanNoort 1992, Compton 1993, Cook & Power 1996, West et al 1996.…”
Section: Resultssupporting
confidence: 67%
“…Pollination is the central service that the wasp provides to the ¢g and the stability of the mutualism depends in part on this service. Some authors have suggested that increased pollination capacity gives a direct positive bene¢t to the pollinator, either by reducing larval mortalities (Galil & Eisikowitch 1971) or by incrementing larval nutrition (Verkerke 1989). A recent study employing careful statistical analyses has shown that pollinators have the highest reproductive success in the fruits that show the highest seed production (Herre & West 1997).…”
Section: (B) Historical Biogeography Of the Mutualismmentioning
confidence: 99%
“…For the ¢g, the loss of pollination behaviour in the wasp does not cause a total loss of pollination and in some cases ¢g wasps are able to develop even in the absence of pollination (Galil & Eisikowitch 1971;Compton et al 1991;Jousselin & Kjellberg 2001). Together, these observations imply that selection for wasps to pollinate actively can be relaxed and that there are costs associated with being an active pollinator.…”
Section: (B) Historical Biogeography Of the Mutualismmentioning
confidence: 99%
See 1 more Smart Citation